2015
DOI: 10.1007/s11102-015-0671-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy and hypophysitis: clinical presentation, treatment, and biologic insights

Abstract: Hypophysitis occurs in a significant minority of patients treated with Ipi, in contrast to the relative rarity of idiopathic autoimmune hypophysitis or hypophysitis after treatment with other immunotherapies. Recently published cohorts have described the clinical presentation and management of IH and longitudinal outcomes in these patients. Additional studies with Ipi and other emerging agents have helped identify potential risk factors for the development of immunotherapy-related hypophysitis and possible und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
287
1
29

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(323 citation statements)
references
References 85 publications
6
287
1
29
Order By: Relevance
“…The average incidence of ipilimumab-induced hypophysitis is 13%, ranging from 1.5 to 17% (Tables 2 and 3) (Faje et al 2014, Faje 2016. In contrast to lymphocytic autoimmune hypophysitis, ipilimumabinduced hypophysitis occurs more frequently in men (Corsello et al 2013, Min et al 2015, Faje et al 2016 and in those of an older age (Faje et al 2014, Faje 2016, even after adjustment of melanoma incidence in male and the elderly. Other associated agents and radiotherapy can alter the risk of hypophysitis induced by ipilimumab, but data are limited (Postow et al 2012, Stamell et al 2013, Shahabi et al 2015.…”
Section: Anti-ctla-4 Mabsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average incidence of ipilimumab-induced hypophysitis is 13%, ranging from 1.5 to 17% (Tables 2 and 3) (Faje et al 2014, Faje 2016. In contrast to lymphocytic autoimmune hypophysitis, ipilimumabinduced hypophysitis occurs more frequently in men (Corsello et al 2013, Min et al 2015, Faje et al 2016 and in those of an older age (Faje et al 2014, Faje 2016, even after adjustment of melanoma incidence in male and the elderly. Other associated agents and radiotherapy can alter the risk of hypophysitis induced by ipilimumab, but data are limited (Postow et al 2012, Stamell et al 2013, Shahabi et al 2015.…”
Section: Anti-ctla-4 Mabsmentioning
confidence: 99%
“…Hypophysitis and hypothyroidism are the most common endocrinopathies, seen in up to 10% of patients treated with anti-CTLA-4 and anti-PD-1/ PD-L1 antibodies (Corsello et al 2013, Topalian et al 2014, O'Donnell et al 2015, Eggermont et al 2016, González-Rodríguez et al 2016, Byun et al 2017. The growing recognition that immunotherapy is potentially associated with endocrine-related adverse events has resulted in higher reported rates of hypophysitis, as clinical suspicion and routine laboratory testing have become a more routine practice (Albarel et al 2015, Min et al 2015, Faje 2016. Clinical suspicion and routine hormone testing are key to the diagnosis of immunerelated endocrinopathies.…”
Section: :12mentioning
confidence: 99%
See 2 more Smart Citations
“…Occasionally, changes of pituitary morphology may precede function or biochemical disturbances; this may resolve after 1-8 weeks of glucocorticoid therapy. 27 The management of hypophysitis primarily involves hormone replacement and consideration of ICIs discontinuation and/or high-dose (immunosuppressive) steroid use. Although congruence between treatment plans is lacking, it is suggested that for patients with grade 1 (mild) hypophysitis, immunotherapy may be continued, while for all other grades of toxicities treatment should be withheld and high-dose systemic steroids (prednisolone 0.5-2mg/kg/day or equivalent), with subsequent tapering to a physiological replacement dose of hydrocortisone or prednisolone, should be initiated (Figure 1).…”
mentioning
confidence: 99%